2016
DOI: 10.1038/nmat4624
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable silicon electronics for transient spatiotemporal mapping of electrical activity from the cerebral cortex

Abstract: Bioresorbable silicon electronics technology offers unprecedented opportunities to deploy advanced implantable monitoring systems that eliminate risks, cost and discomfort associated with surgical extraction. Applications include post-operative monitoring and transient physiologic recording after percutaneous or minimally invasive placement of vascular, cardiac, orthopedic, neural or other devices. We present an embodiment of these materials in both passive and actively addressed arrays of bioresorbable silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
353
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 425 publications
(379 citation statements)
references
References 43 publications
3
353
0
3
Order By: Relevance
“…In an advanced example, actively multiplexed sensor arrays in thin flexible formats allow mapping of electrical activity on the surface of the brain with spatial and temporal high resolution. 97 Figure 8b (left) shows a representative device that consist of 64 separate sensing electrodes and 24 wires as interfaces to external data acquisition systems. An important benefit of actively multiplexed readout, enabled by Si NM-based transistors at each electrode, is that it greatly reduces the number of wires needed for acquisition, which is particularly important at high channel counts.…”
Section: Physically Transient Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an advanced example, actively multiplexed sensor arrays in thin flexible formats allow mapping of electrical activity on the surface of the brain with spatial and temporal high resolution. 97 Figure 8b (left) shows a representative device that consist of 64 separate sensing electrodes and 24 wires as interfaces to external data acquisition systems. An important benefit of actively multiplexed readout, enabled by Si NM-based transistors at each electrode, is that it greatly reduces the number of wires needed for acquisition, which is particularly important at high channel counts.…”
Section: Physically Transient Electronicsmentioning
confidence: 99%
“…Delay map for the bandpass filtered data of epileptic spike activity (right). Reprinted with permission from Yu et al 97 Copyright 2016 Nature Publishing Group…”
Section: Additional Informationmentioning
confidence: 99%
“…Recent next-generation advances in miniaturized hermetic sealing of silicon integrated circuits, such as multilayer multimaterial coating [187], and encapsulation using liquid crystal polymers (LCPs) [185], are promising developments toward highly miniaturized implantable electronics for chronic clinical use. Furthermore, recent advances in dissolvable flexible electronics [188], [189] offer alternatives to hermetic encapsulation for acute applications without the need for post-use surgical extraction. Fig.…”
Section: Hermetic Encapsulationmentioning
confidence: 99%
“…As the core of neurophysiologic monitoring, realizing high‐quality signal collection is an important topic in the research of neural electrode arrays. Related researches have indicated that stretchable/flexible neural electrode arrays, with their excellent mechanical and electrical performance, are superior candidates for the next generation of implantable devices 3, 4, 5, 6, 7, 8, 9, 10, 11. The successful development of stretchable/flexible neural electrode arrays hinges on good conformal contact between the array and the tissue, which enables excellent mechanical and electrical properties,3 as well as low‐cost, stable, and high‐throughput manufactural techniques.…”
Section: Introductionmentioning
confidence: 99%